Bonnie and Clyde Revisited: A Conceptual Model of the Behavior of the Instigators of the GameStop Short Squeeze of 2021 - Samsa, Greg (Archives of Business Research, 2021)
The efficient market hypothesis assumes that investors act independently, but social-media-enabled behavior among amateur investors demonstrably violates this assumption. This was dramatically illustrated by a recent short squeeze in the shares of GameStop. By analogy with conceptual models in the behavioral sciences, we outline a conceptual model attempting to explain the behavior of the participants, and explore some of the implications of this conceptual model for investors. This case study illustrates a systematic inefficiency in option pricing which only become apparent when extreme market conditions are encountered. Although the cognitive biases of amateur investors are of little importance for understanding stock prices, this is a special case where their cognitive biases do matter.